Government Spending and Islamic HDI: Evidence of Islamic Sharia Implementation in Indonesia - Chandra, Ade; Fadly, Fajar; Wardani, Tri Ulfa (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study aims to see the extent of the application of Islamic law by looking through indicators of human quality measurement based on sharia maqashid known as the Islamic Human Development Index (IPT) compared to the Human Development Index (HDI) based on the realization of government expenditure consisting of education functions, health functions, economic functions, infrastructure functions, social protection functions, environmental functions, order and security, tourism and cultural functions in Aceh Province as one of the provinces in Indonesia have implemented Islamic Law. Method – This study uses panel data with 277 observation data consisting of 23 districts and cities in Aceh Province with a period of 2013 - 2024. The approach used was multiple linear regression with an analysis tool using Eviews 12. Findings – The results of the study show that government spending simultaneously has a significant effect on IHDI and HDI. Government spending on infrastructure and environmental functions has a significant influence on IHDI. Meanwhile, in conventional human development, there is not a single expenditure function that has a significant effect on HDI. Implications – Examine the extent to which government spending can contribute to the enforcement of Islamic sharia in Indonesia's specific regions.